Camp Nova 2024 A Transformative Experience in English Communication - Amy Zulaikha, Mohd Ali; Noraisah Nurul Fatwa, Mohd Razali (UMPSA, 2024)
Camp Nova 2024, an intensive three-day programme designed to elevate English proficiency among Matriculation Programme students, concluded successfully from 27th to 28th September 2024. Organised by the Centre for Modern Languages (CML), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) the camp was held at Pekan.